Perlindungan Hukum Terhadap Rahasia Dagang Obat-Obatan Tradisional Atas Pemanfaatan Tanpa Hak dalam Sistem Hukum Hak Kekayaan Intelektual Indonesia - Siti Hamidah (Program Studi Magister Ilmu Hukum Universitas Islam Nusantara, 2017)
Secret commerce Protection, be accepted by the community industry, but instead secret commerce protection is still not entirely accepted by traditional communities in which their relations are still based on traditional ties. Traditional medicines have long been